Panagia Portaïtissa of Kydonies / Ayvalık: the Consequences of the 1923 Population Exchange for a metochion of the Athonite Monastery of Iveron - Vanessa R. de Obaldía (Cahiers Balkaniques)
Abstract: a late 19th century former Rum Orthodox shrine and Athonite metochion stands in the old quarter of the Aegean coastal city of Ayvalık / Kydonies. Once graced with the name Portaïtissia [Πορταϊτίσσηα] in dedication to the icon of Panagia Portaïtissa (Our Lady the Gatekeeper) preserved at Iveron Monastery, the stone building, monks’ quarters, and surrounding garden are private property. Important information from unpublished archival sources written in Ottoman Turkish and Greek sheds new light on a sacred site formerly insufficiently analysed through secondary narratives. Accordingly, multiple layers of the unconventional history of the shrine shall be uncovered during the turmoil of the late Ottoman and early Republican eras until today. The objective of this study is twofold. Firstly, to reveal the material consequence of the population exchange for Christian Orthodox places of worship through the little-studied case of a former metochion belonging to the 10th century Athonite monastery of Iveron. Secondly, to understand the relations between the Mount Athos, the Ottoman Empire and later the Turkish Republic during two consecutive eras and the complex consequences of the 1923 Lausanne Treaty’s article of the Population Exchange on Christian Orthodox places of worship, and specifically Athonite metochia.